Global corporate governance - John, Kose; Makhija, Anil K.; Ferris, Stephen P. (Emerald Publishing Limited, 2017)
Advances in Financial Economics Volume 19 deals with International Corporate Governance, particularly the role played by boards of directors, internal organization design and governance mechanisms, franchise agreements, the effect of regulation and policy, the market for corporate control, and strategic alliances.
Prelims -- Financial performance and the competitive effects of corporate social responsibility -- Regulation and the ownership structure of European listed firms -- Determinants of corporate leverage in publicly listed GCC companies - Conventional versus Sukuk -- Large shareholders and target returns: international evidence -- A gender gap in executive cash compensation in Thailand: A view of the expectancy theory -- CEO Compensation practices around spinoffs -- Socio-psychological motives of socially responsible investors -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Business & Economics -- Corporate Governance; Economics; Corporate governance